The Sociological Dimensions of the FCP Method: A Christian Psychotherapy Approach to Addressing Stress and Suffering. - Ilievski, Naum; Angelina Ilievska, MD (European Journal of Social Science Education and Research, 2024)
The concept of the Five Control Points, FCP (systematized by the author), is a contemporary approach used in Christian Psychotherapy that arises from a specific personal and spiritual experience under the supervision of a spiritual father—psychotherapist. It enables productive and meaningful overcoming of stress, as well as of the process of suffering, on a personal and wider social level, developing an adaptive social response and effective functioning. This is a descriptive study of the applied FCP method. It consists of five control points based on the Christian spiritual practice (acceptance, thanksgiving, self-discernment, quiescence and prayer). In the classical approaches, dealing with stress occurs on a psychological level by activating the psychological defence mechanisms, the most common: suppression, denial, rationalization. With FCP there is a completely opposite reaction. The intrapsychic process and its dynamics shift in the domain of the spiritual self with phenomenon of positive transformation (metanoia). The FCP method stimulates a creative process of overcoming stress and suffering as a purposeful and useful integrated experience that enhances the capacity of existence by enabling further and continuous personal growth and development. The person maturing through this process is the unifying axis, the peacemaker and the pointer to the positive developmental direction in the family unit, the environment and the society as a wider context. The positive social impact of the concept can be observed by comparing the usual human behaviour and the behaviour of a person trained through the FCP method.